O comportamento social da personagem Luzia em Luzia homem de Domingos Olímpio - PAIXÃO, Maria Orlandina Batista (2024)
The objective of the article is to analyze the social behavior of the character LUZIA in LUZIA HOMEM by Domingos Olímpio, it is to present the figure of the woman, using the character Luzia from the work Luzia Homem by Domingos Olímpio (1903), as a basis to illustrate the feminine behavior within the northeastern social context of the 19th century. How do they reveal actions contrary to the conventions of the period and show how women are treated and whether their behavior is in line with what was expected at the time